2020
DOI: 10.2147/clep.s251710
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Patients with New-Onset Heart Failure and Reduced Ejection Fraction in Danish Administrative Registers</p>

Abstract: Background: In Danish administrative registers, ejection fraction (EF) is not recorded, which is a considerable limitation for correct subclassification of patients with heart failure (HF). We hypothesized that a diagnosis of HF combined with the recorded prescription of both renin-angiotensin system (RAS) inhibitors and beta-blockers (RASi+BB) within 120 days could identify patients with HF and reduced ejection fraction (EF ≤40%) (HFrEF). Methods: On two sites, we identified all patients with a first-time reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Our study is based on data from administrative registries and therefore it should be noted that data on LVEF are not available. Our used definition of HFrEF is based on a previous published methodological study that proposed that HFrEF patients could be identified in Danish registries with the definition used in the present study 14 . Though, we cannot further evaluate the association between mildly and severely reduced LVEF and MRA adherence/persistence, which is an important limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is based on data from administrative registries and therefore it should be noted that data on LVEF are not available. Our used definition of HFrEF is based on a previous published methodological study that proposed that HFrEF patients could be identified in Danish registries with the definition used in the present study 14 . Though, we cannot further evaluate the association between mildly and severely reduced LVEF and MRA adherence/persistence, which is an important limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous validation study has shown that this HFrEF definition has a high positive predictive value (95%), and that the sensitivity and specificity are 85%. 14 Therefore, some HFrEF patients are overlooked, but only few HFpEF patients included. According to the definition (120 days after the diagnosis HF), the sickest patients might have died before study start.…”
Section: Study Population and Outcomesmentioning
confidence: 99%
“…However, the definition used for the study population in the sensitivity analysis, which yielded results similar to the primary analysis, has a positive predictive value of 95% in the Danish registries to identify patients with HF and reduced ejection fraction. 27 Compared with the population in the study by Stewart et al 37 of ambulatory patients with advanced HF on oral medical therapy with high risk features, our cohort of patients in the sensitivity analysis were similar regarding age (median 65), sex (72% males) and cohabitant status (65% living together), although ischemic heart disease (38% versus 46%) and number of patients on loop diuretics (64% versus 95%) were less frequent in our cohort. In the group referred to RHC, 82% of the patients had filled prescriptions of loop diuretics.…”
Section: Variablementioning
confidence: 52%
“…This definition has been shown to capture the majority of new‐onset HFrEF in our registries (defined as a left ventricular ejection fraction ≤40%), with a sensitivity of 85% and a positive predictive value of 95%. 20 We stratified data by T2D status, defined as a diagnosis of diabetes ( ICD E11, E14), excluding type 1 diabetes ( ICD E10), or a claimed prescription of at least one hypoglycemic agent within 120 days of HF diagnosis. Incident T2D was defined by the same criteria.…”
Section: Methodsmentioning
confidence: 99%